Towards the National Vision Policy: Review of the New Economic Policy and New Development Policy Among the Bumiputera Communities in Sabah - Bilson Kurus,; Wilfred M. Tangau, (Kajian Malaysia, 2003)
Over the last decade, Vision 2020 has served as the guiding light in the sea of development in Malaysia. Vision 2020 has also come to symbolise Malaysia's "can do" spirit as it steadily steers it own course in the midst of the globalisation and liberalisation waves. In this respect, Vision 2020 has in effect become the country's beacon as Malaysia presses onward towards the ultimate goal of achieving a developed nation status in its "own mould" by the year 2020. With less then 20 years to go before the year 2020,it is perhaps fair to ask if the nation is on course to achieve the ultimate goal of Vision 2020. While the country has made rapid progress and continues to make good progress in key areas such as the transformation of the economy from an agricultural based to industrial based and more important, to the emerging requirements of the digital and K-economy, there is still a lot of ground to cover in the short span of time towards 2020.